Improvement of Anxiety, Coughing, Breathlessness and Pain Control in The Management of Bronchoscopy by Adding Alprazolam - Yanny Octavia Sally Ride; Yusup Subagio Sutanto; Debree Septiawan (Jurnal Respirologi Indonesia, 2019)
Background: Anxiolytic premedication can reduce anxiety, improving procedural tolerance, and reduce postbronchoscopic complications. There was ongoing debate about the safety of bronchoscopist-administered sedation. Alprazolam as a surgical premedication can reduce anxiety. Alprazolam can be used as an adjuvant analgesic, to reduce anxiety-related breathlessness, and to reduce coughing as adjuvant antitussive. The study aimed to evaluate the effectiveness of alprazolam in patients undergoing bronchoscopy. Methods: A clinical study with experimental quasi pre-post test control group design, using consecutive sampling was performed in patients with lung tumor undergoing bronchoscopy in dr.Moewardi Hospital from February to March 2019. The study subjects were divided in experimental (alprazolam) and control groups (without alprazolam). The Hospital Anxiety and Depression Scale (HADS), VAS for pain score, modified Borg score, and VAS for cough were measured in baseline, before, and after bronchoscopy. Results: Thirty two lung subjects were included in this study. The intervention groups showed decreased HADS score pre and post bronchoscopy (6.56±2.83 and 6.88±2.63), pain VAS scores (15.00±10.95 and 9.69±11.61), cough VAS score (11.56±8.89 and 27.19±17.89), and these were different significantly compared to control group. We found decreased mean of modified Borg in the study group though they were not significant compared to the control group. Conclusion: Alprazolam controlled anxiety, coughing, and pain in patients undergoing bronchoscopy. Alprazolam minimized breathlessness after bronchoscopy. (J Respir Indo. 2019; 39(4): 245-55)